Measuring student experience : relationships between Teaching Quality Instruments (TQI) and Course Experience Questionnaire (CEQ) : evaluation report. - Rochecouste, Judith (Australian Learning and Teaching Council (ALTC), 2011)
Evaluation report of a project that focused on quality assurance measures in Australian universities. Graduate and enrolled students' experiences were investigated by analysing the relationship between student responses in Teaching Quality Instruments survey data and course experience questionnaire data.